2014
DOI: 10.1155/2014/248187
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral Ear Occlusion for Improving the Reliability of Otoacoustic Emission Screening Tests

Abstract: Newborn hearing screening is an established healthcare standard in many countries and testing is feasible using otoacoustic emission (OAE) recording. It is well documented that OAEs can be suppressed by acoustic stimulation of the ear contralateral to the test ear. In clinical otoacoustic emission testing carried out in a sound attenuating booth, ambient noise levels are low such that the efferent system is not activated. However in newborn hearing screening, OAEs are often recorded in hospital or clinic envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…However, Boothalingam et al (2014) found a trend of reduced contralateral inhibition of otoacoustic emissions (OAEs) elicited with single-tone stimuli (stimulus frequency OAEs) when the tones were AM versus unmodulated. No significant differences were seen in contralateral inhibition when elicited by a babble noise relative to white noise (Timpe-Syverson and Decker, 1999;Papsin et al, 2014), but these studies did not report sufficient controls for middle-ear muscle reflex activation which could interfere with the interpretation of results (Goodman et al, 2013) and the click stimulus rate of 50/s may have elicited the ipsilateral MOCR (Boothalingam and Purcell, 2015). A recent paper examined the effect of a variety of contralateral noises on contralateral inhibition (Kalaiah et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, Boothalingam et al (2014) found a trend of reduced contralateral inhibition of otoacoustic emissions (OAEs) elicited with single-tone stimuli (stimulus frequency OAEs) when the tones were AM versus unmodulated. No significant differences were seen in contralateral inhibition when elicited by a babble noise relative to white noise (Timpe-Syverson and Decker, 1999;Papsin et al, 2014), but these studies did not report sufficient controls for middle-ear muscle reflex activation which could interfere with the interpretation of results (Goodman et al, 2013) and the click stimulus rate of 50/s may have elicited the ipsilateral MOCR (Boothalingam and Purcell, 2015). A recent paper examined the effect of a variety of contralateral noises on contralateral inhibition (Kalaiah et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One study suggested that if OAE tests are performed in noisy environments (above 55 dB SPL), it is strongly recommended to occlude the contralateral ear. 59…”
Section: Neonatal Hearing Loss–related Screeningmentioning
confidence: 99%